Precise tailoring of multiple nanostructures based on atomic layer assembly via versatile soft-templates. (June 2021) - Geng, Guangzhou; Zhu, Wei; Pan, Ruhao; Zhang, Zhongshan; Gu, Changzhi; Li, Junjie
Highlights: Atomic layer assembled nanofabrication (ALAF) can break through the limitations of conventional lithography. Soft-templates based ALAF has more advantages in freely tuning the size, shape and spatial arrangement of nanostructures. Atomic layer assembly via versatile soft-templates can precisely tailors multiple nanostructures with various materials. ALAF endows the nanofabrication with new powerful functionalities and more scalabilities. Graphical Abstract: ga1 Abstract: Nanodevices have higher requirements for nanofabrication in tuning the size, shape and spatial arrangement of nanostructures and their assemblies in nanoscale, however, which are often beyond the reach of conventional lithography or self-assembly techniques. In view of the above, we develop atomic layer assembled nanofabrication based on soft-templates to break through the limitations of traditional rigid-templates, having very well scalability and powerful fabrication capability for multiple solid or hollow nanostructures. Versatile soft-templates can be freely patterned at the nanoscale by mature lithographic processes, along which a precisely controlled atomic layer deposition can assemble high-aspect-ratio nanostructures with a flexible tailoring of the size, shape and spatial array, and then a dry etching process removes soft scaffolds and leaves freestanding nanostructures over large-area, rigid or soft substrates. To highlight the potentials of this fabrication strategy, the high-performance optical metasurface and ultra-sensitive H2 gas sensor are demonstrated. This approach endows the conventional lithography and assembly techniques with new powerful functionalities and more scalability in nanofabrication, providing a simply promising route to generating complex multiple nanostructures, towards a broad application in modern nanodevices.